تأثير تغير طاقة الرص على نفاذية التربة الرملية المعالجة بالشمع لاستخدامها في تبطين أرضية المطامر( حالة مطمر البصة باللاذقية ) - وائل حرفوش; رامي أسطه; ديمه سلامه (Tishreen University, 2018)
يشكل وجود المطامر غير النظامية مصدرا خطيرا لتلوث التربة والمياه الجوفية بالرشاحات الناتجة عن النفايات المتزايدة. هناك العديد من الأبحاث التي تدرس فعالية مواد مختلفة كالاسمنت و البنتونايت و البوليميرات وحديثا" الشمع في تكتيم المطامر الصحية ، وقد أظهر استخدام الشمع كفاءة عالية مقارنة ببقية المواد فهو يتمتع بمقاومة كيميائية عالية فلا يتحلل مع الوقت ولا يتأثر بالعصارة الناتجة عن النفايات ويمكنه تخفيض نفاذية التربة لدرجة تصل أحيانا" حتى الكتامة التامة. تتعلق نفاذية التربة المعالجة بالشمع بشكل أساسي بطاقة رص التربة و بنسبة الشمع المضافة إلى التربة . يهدف البحث إلى دراسة تأثير تغير طاقة الرص على نفاذية التربة الرملية المعالجة بنسب من الشمع والوصول إلى تحديد النسبة المثلى للإضافة الموافقة لطاقة الرص المحققة للنفاذية المطلوبة في المطامر. تم اختيار مطمر البصة كون تربة الموقع رملية نفوذة ومنسوب المياه الجوفية مرتفع وهناك خطورة من تسرب العصارة السائلة ضمن التربة وتلوث المياه الجوفية. The presence of unregulated landfills provides a dangerous source of soil and groundwater contamination because of leachates resulting from ever-increasing waste. Prior research has been undertaken to study the effectiveness of impermeability of materials such as cement, bentonite, polymers and recently wax. The use of wax proved high efficiency, this is because it possesses high chemical resistance ,does not degrade with time ,and is not affected by waste leachates. furthermore, wax was capable of reducing the permeability of soil to the point of complete impermeability. The permeability of soil treated with wax depends mainly on the soil compaction effort and the percentage of wax content added to the soil. This research aims to study the effect of compaction energy variation on permeability of sandy soil treated with wax and determine the optimum ratio for the addition of wax to achieve the required impermeability in landfills. Al Bassa landfill was selected because of its sandy permeable soil and its high water table level where there is a risk of contamination by leakage of leachate into the soil and groundwater.